REPURPOSING ORLISTAT AS A FATTY ACID SYNTHASE INHIBITOR IN BREAST CANCER: IN VITRO EFFICACY, MECHANISMS, AND SYNERGY WITH DOXORUBICIN - Rasool, Abeer Mansour Abdel; Rashid, Ammar M. Sheet; Hassan , Emad Hussein Ahmad; Subhi, Abdulhameed (PT. Antis International Publisher, 2026)
Objective: This study investigates the therapeutic potential of repurposing Orlistat, a potent irreversible inhibitor of fatty acid synthase (FASN), to enhance cytotoxic efficacy against breast cancer cells, both independently and in combination with doxorubicin. Method: Estrogen receptor-positive MCF-7 and triple-negative MDA-MB-231 cells were treated with Orlistat and doxorubicin individually and jointly, followed by assessments of cell viability (MTT), FASN expression (qRT-PCR and Western blot), apoptosis (Annexin V-FITC/PI flow cytometry and cleaved caspase-3), and drug interactions using the Chou–Talalay combination index. Results: Orlistat monotherapy significantly reduced cell viability in a dose-dependent manner, induced G1 arrest and apoptosis, and suppressed FASN expression and lipid accumulation, confirming metabolic targeting. Doxorubicin alone produced expected cytotoxicity, whereas the Orlistat–doxorubicin combination yielded synergistic inhibition (CI < 1) with markedly enhanced apoptotic signaling. Novelty: This work demonstrates, for the first time, a robust synergistic interaction between Orlistat and doxorubicin through coordinated disruption of lipid metabolism and heightened apoptotic induction, highlighting Orlistat’s promise as a metabolic adjuvant to improve breast cancer chemotherapeutic responses.